The Role of Modern Linguistics in the Learning of Arabic Language Skills - Mizan, Khairul; Arjuna, Ibnu Hajar; Atiq, Abdian Akbar; Wargadinata, Wildana (Institut Agama Islam Negeri Palopo, 2023)
Modern linguistics plays an important role in learning Arabic language skills. So this study aims to describe the role of modern linguistics in learning Arabic language skills. This study uses a qualitative approach with descriptive methods with the type of library research. The results of this study indicate that modern linguistics has an important role in learning Arabic language skills, namely in phonological analysis, understanding, analyzing, and applying phonological principles in studying sound systems in Arabic; analysis of morphology and word formation, to understand morphological structures, word formation rules, morpheme meanings, morphological variations, and morphological patterns in Arabic; analysis of syntax and sentence structure, to analyze syntax and sentence structure in more depth; analysis of semantics and word meanings, to understand word meanings and semantic structures in language; and pragmatic analysis and use of language to understand how language is used in social and communicative interactions. So it can be concluded that modern linguistics plays an important role in phonological analysis, morphological analysis and word formation, analysis of syntax and sentence structure, analysis of semantics and word meanings, and pragmatic analysis and use of language.